Assessing the relationship between information transparency through social media disclosure and firm value / Abdalmuttaleb M.A Musleh Al-Sartawi - M.A Musleh Al-Sartawi, Abdalmuttaleb (Accounting Research Institute (ARI), Shah Alam, 2019)
The aim of this paper is to show the relationship between social media financial disclosure and firm value of the GCC listed firms. To answer the research questions, the researchers collected cross-sectional data from a sample of 241 firms listed in the financial stock markets of the GCC for the year 2017. An Index was used to calculate the total level of social media financial disclosure where the SMFD for each firm was calculated by dividing the total earned scores of the firm by the total maximum possible scores appropriate for the firm. The findings show that the 84% of firms in the GCC countries use social media, while 70% of these firms use the SM for financial disclosure. The results also confirm the hypothesis that enhanced disclosure levels through various social media channels of GCC listed firms significantly influence the firm value of these firms. These results have implications for both the social media disclosure literature and value relevance literature in the GCC countries.